Analisis Peluang dan Ancaman Ekspor Kacang Hijau: Studi Kasus Indonesia dan Filipina Tahun 2025 - Anisa Fitriani (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
This study analyzes the opportunities and threats of mung bean export from Indonesia to Filipina in 2025. Mung bean is a strategic agricultural commodity with high nutritional and economic value, contributing to both domestic consumption and international trade. This research applies a descriptive method using a mixed approach, combining quantitative data from Pusat Data dan Sistem Informasi Pertanian and qualitative analysis through literature review. The findings reveal that the Philippines presents significant export opportunities due to high domestic demand, limited local production, and growing food consumption, supported by regional cooperation within ASEAN, geographical proximity, and similar consumption patterns. However, challenges such as intense competition from other exporting countries, non-tariff barriers, price sensitivity, and inefficiencies in Indonesia’s supply chain remain critical constraints. In addition, global price fluctuations and changing trade policies contribute to export uncertainty. Therefore, improving productivity, product quality, supply chain efficiency, and market diversification is essential to enhance Indonesia’s competitiveness and sustain its agricultural exports in the regional market.